Age of anxiety meaning, identity, and politics in 21st century film and literature - Wachs, Anthony M., 1983- (Politics, literature, & film., 2019)
"Age of Anxiety: Meaning, Identity, and Politics in 21st Century Film and Literature applies historical and contemporary political and rhetorical theory to current popular culture to discuss the problem of the displaced autonomous self and the quest for a meaningful life"--